(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, the methods of developing the professional competence of future directors based on literary works in audience training are researched, in which the methods of developing the professional competence of future directors based on training exercises, on the basis of drabbles, on the basis of etudes, on the basis of dramatic fragments, on the basis of dramatic works are highlighted.